The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1038/s41598-017-02032-4
|View full text |Cite|
|
Sign up to set email alerts
|

Orbital angular momentum analysis for giant spin splitting in solids and nanostructures

Abstract: Giant spin splitting (GSS) of electronic bands, which is several orders of magnitude greater than the standard Rashba effect has been observed in various systems including noble-metal surfaces and thin films of transition-metal dichalcogenides. Previous studies reported that orbital angular momentum (OAM) is not quenched in some GSS materials and that the atomic spin-orbit interaction (SOI) generates spin splitting in some solid states via the interorbital hopping. Although the unquenched OAM may be closely re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 59 publications
1
15
0
Order By: Relevance
“…In the case of bulk, the spin-orbit coupling has relatively small effect compared with 2D layers. Also, the spin splitting in the conduction band is much smaller than that in the valence band because the enhancement of the spin splitting in 2D TMDs is due to the orbital angular momentum generated by the broken mirror symmetry [56]. Thus, for few-layer systems, the giant spin splitting raises the VBM at the K point, resulting in a direct band gap if the CBM is also at the K point.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of bulk, the spin-orbit coupling has relatively small effect compared with 2D layers. Also, the spin splitting in the conduction band is much smaller than that in the valence band because the enhancement of the spin splitting in 2D TMDs is due to the orbital angular momentum generated by the broken mirror symmetry [56]. Thus, for few-layer systems, the giant spin splitting raises the VBM at the K point, resulting in a direct band gap if the CBM is also at the K point.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the existence of non-zero hL Z i, valley spin splitting occurs when considering the strong SOC of Mo. 45,46…”
Section: Lattice Structure and Stabilitymentioning
confidence: 99%
“…39 Therefore, the thermodynamic stability of BMPI with surface-adsorbed H 2 O relative to the intercalated case is of primary importance for photocatalyst applications while the H 2 O migration energy barrier needs to be high as well. To improve the stability, one can consider effective ways of modulating the electronic structure of low-dimensional materials such as applying an external electric eld ( Ẽext ), [43][44][45] chemical doping [46][47][48] as well as encapsulation. [49][50][51][52][53] Several studies have been reported such that the efficiency of catalysts is improved using the external eld by modulating the chemical reactivity 54,55 such as eld-assisted catalysts 56,57 and bipolar electrochemical cells.…”
Section: Introductionmentioning
confidence: 99%